Progesterone therapy in women with intractable catamenial epilepsy - Mohammadreza Najafi; Maedeh Mirmohamad Sadeghi; Jafar Mehvari; Mohammad Zare; Mojtaba Akbari (Advanced Biomedical Research, 2013)
Background: Catamenial epilepsy is a kind of epilepsy, known in this name, when the periodicity of the exacerbation of the seizure is in association with menstural cycle. The present study examined the progesterone effectiveness as a complementary treatment in women with intractable catamenial epilepsy. Materials and Methods: The present study was conducted as a double-blind randomized controlled trial on 38 women with intractable catamenial epilepsy. Patients were assessed in two groups: The case group received in addition to AEDs, two (Mejestrol) 40 mg progesterone tablets in the second half of the cycle from 15 th to 25 th day. And the control group received in addition to AEDs, two placebo tablets daily. Age, BMI, epilepsy duration, types of the drugs used, progesterone level, and the number of the seizures in 3 months before and after the study were compared. Results: Based on the results of which there was no statistically significant difference in regard to age, BMI, epilepsy duration, types of the drugs used, progesterone level between the case and the control groups (P-value > 0.05). The number of the seizures after treatment has significantly decreased compared to before-treatment state. The degree of decreasing in the case group receiving the progesterone was higher than in the control group receiving the placebo. The difference, thus, is significant, based on statistical tests (P-value = 0.024). Conclusion: Based on the findings of this study using progesterone in women with intractable catamenial epilepsy has a significant effect on the degree of decreasing in the number of the seizures.